1985
DOI: 10.1111/j.1558-5646.1985.tb04083.x
|View full text |Cite
|
Sign up to set email alerts
|

GENOMIC COADAPTATION AND DEVELOPMENTAL STABILITY WITHIN INTROGRESSED POPULATIONS OFENNEACANTHUS GLORIOSUSANDE. OBESUS(PISCES, CENTRARCHIDAE)

Abstract: Using fluctuating bilateral asymmetry as a measure of developmental stability, we tested the hypothesis that genomic coadaptation mediates developmental stability in natural populations. Hybrid populations were more asymmetrical than populations of the parental species, and ranks of overall developmental instability were positively correlated with ranks of mean heterozygosity in these populations. The failure to find increased asymmetry in previous studies of natural hybrid populations (Jackson, 1973a, 1973b; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 37 publications
4
31
0
2
Order By: Relevance
“…cucullata was developmentally more unstable than the other two taxa. In earlier empirical studies, both animal and plant hybrids have shown greater variability and less developmental stability than their parent populations (Strauss 1987;Ross and Robertson 1990;Graham and Felley 1985;Leary et al 1985). D. cucullata´galeata hybrids, however, displayed equal levels of developmental instability to D. galeata and less developmental instability than D. cucullata.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…cucullata was developmentally more unstable than the other two taxa. In earlier empirical studies, both animal and plant hybrids have shown greater variability and less developmental stability than their parent populations (Strauss 1987;Ross and Robertson 1990;Graham and Felley 1985;Leary et al 1985). D. cucullata´galeata hybrids, however, displayed equal levels of developmental instability to D. galeata and less developmental instability than D. cucullata.…”
Section: Discussionmentioning
confidence: 88%
“…Developmental instability is random variation in individual development and is de®ned as phenotypic variation among individuals with identical genotypes living in an uniform environment (Scheiner et al 1991;Yampolsky and Scheiner 1994). It is generally assumed that genomic coadaptation and heterozygosity are the two genetic factors that increase developmental stability (Graham and Felley 1985). Hybrid populations are therefore thought either to bene®t from an increase in heterozygosity or to suer from disruption of coadaptation, depending on the degree of divergence between hybridising taxa (Harrison 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In this species, the presence of an unmodified resistance allele disrupts developmental stability and elevates FA through the breakdown of genic coadaptation. Evidence for a similar general mechanism elevating FA comes from hybridization studies of stickelbacks (Pungitius), sunfishes (Enneacanthus), fruit flies (Drosophila), and willows (Salix; Tanaka 1982; Graham and Felley 1985;Markow and Ricker 1991;Hochwender and Fritz 1999). But increasing genetic diversity within species may have a very different outcome; in rainbow trout (Oncorhyncus mykiss), cutthroat trout (O. clarki), and house mice (Mus musculus), the most heterozygous individuals express the least FA (Leary et al 1983(Leary et al , 1984Alibert et al 1994).…”
mentioning
confidence: 98%
“…Literature is replete with studies concerning FA in hybrids (and comparison with parents) and the results are a mixed bag (Jackson 1937a, b;Felly 1980;Zaharov 1981;Graham and Felly 1985;Leary et al 1985;Ferguson 1986; Lamb and Avise 1987;Ross and Robertson 1990;lamb et al 1990;Markow and Ricker 1991;Graham 1992;Blows and Sokolowaki 1995;Hutchinson and Cheverud 1995;Alibert et al 1997;Andersen et al 2002Andersen et al , 2006Andersen et al , 2008Rego et al 2006;Carreira et al 2008;Vishalakshi and Singh 2009;Demontis et al 2010;Trotta et al 2010;Novicic et al 2011). Alibert and Auffray (2003) said that 71 % published work show an increase in FA in hybrids (of different genera, or species) from parents.…”
Section: Discussionmentioning
confidence: 96%
“…In some of the studies, natural hybrid populations (mostly insects, fish, frogs and lizards) were examined. It has been postulated by Graham and Felly (1985) that the age of the hybrid zone determines whether hybrids will have a greater or lesser FA than the parental populations. If they have existed for a long while, coadapted gene complexes having had time to evolve, would rescue any dire effect on FA.…”
Section: Discussionmentioning
confidence: 99%